Teaching of Geometry with GeoGebra Software in High School Students of an Educational Institution in Lima - Diaz-Nunja, Luis (2018)
The study evaluated the effects of the use of GeoGebra software in the teaching of geometry with high school students in the development of their capacities for reasoning and demonstration, mathematical communication and problem-solving. The framework of the study was the increasing presence of technologies in the school teaching of mathematics in young people of the digital age, in a context where education favors the active participation of students in the strengthening of their own abilities. The students were observed in two groups, the group intervened exposed to the use of GeoGebra software and the control group exposed to traditional teaching without the use of the software. Both groups were evaluated with a Geometry Learning Assessment Test that was applied before and after the intervention. The results suggest that the use of the GeoGebra software had effects in the strengthening of the three capacities, with improvements that were significant at high levels. Also, the scores reached at the time afterwards were favorable to the group intervened in the three capacities, with significant differences at moderate levels.